Mythological Aspects of Supreme Power Concept by Eusebius Pamphilus - Savelieva, Marina (Conatus - Journal of Philosophy, 2024)
The article deals with one of the earliest Christian interpretations of the supreme secular power created by Eusebius Pamphilus, Bishop of Caesarea, during the life of the first Christian emperor Constantine the Great. It is proved that the concept by Eusebius contains mythological ideas transformed in a Christian context. In particular, the main focus of the interpretation of the Lord is the recognition of Him as Pantocrator [Παντοκράτωρ – the Lord of all] endowed with infinite power and authority over the Universe. Such an interpretation reconstructs archaic ideas about the deity as the centre of power and says nothing about his mercy and justice. This concept became the basis for the argumentation of the absolute nature of the Christian emperor’s supreme power – Basileus. The Lord, communicating with Basileus through His Son, Christ the Logos, gives him the sacred right to reign and thus makes him godlike [Friend of God – Θεóς, divinely favoured] – an icon of the Lord of all. Another mythological feature of Eusebius’ interpretation of supreme power is the solution to the problematic relationship between the reign and the priesthood. Eusebius believed that the Lord’s endowment of Basileus with the right to reign obliges him to perform priestly functions at the same time. The purpose of Basileus’ priesthood was to enlighten his flock about the essence of the Word of God, and not to observe religious rituals. In this way, the role of the basileus-priest differed from the Patriarch. Thus, the mythological nature of the concept by Eusebius of Caesarea is the fact that he unconsciously replaced various semantic connections. This happened because he could not explain the essence of supreme power and its value to society in a different way. The foundation of Eusebius’ mythological thinking is the beginning of the synthesized rationality (historical understanding of the real past) and myth (substitution of history by religious tradition) of the history of the Byzantine Empire.